(untitled) (Palimpsesto, 2025)
Research progress of a postdoctoral project that seeks, through a dual dialogue between philosophy and theater (object and focus), to analyze the poetics of theater director Manuela Infante, in what has been termed here as the first and second stages. This section represents a division between two distinct philosophical sensibilities, which can understand each other as a whole. The period encompassed by both stages runs from 2002 to 2024, comprising a corpus of twelve works premiered in Chile during those two decades. This arc, also understood as historical, allows us to consider the evolution of Infante’s work as a paradigmatic case of the development of contemporary theater in Santiago de Chile and the relationship between philosophy and theater.